The Puzzle of Persistently Negative Interest Rate-Growth Differentials : Financial Repression or Income Catch-Up? - Shabunina, Anna (IMF Working Papers; Working Paper ;, 2011)
The interest rate-growth differential (IRGD) shows a marked correlation with GDP per capita. It has been on average around 1 percentage point for large advanced economies during 1999-2008; but below -7 percentage points among non-advanced economies - exerting a powerful stabilizing influence on government debt ratios. We show that large negative IRGDs are largely due to real interest rates well below market equilibrium - possibly stemming from financial repression and captive and distorted markets, whereas the income catch-up process plays a relatively modest role. We find econometric support for this conjecture. Therefore, the IRGD in non-advanced economies is likely to rise with financial integration and market development, well before their GDP per capita converges to advanced-economy levels.